Enhancement of the Accountability of Public Sectors through Integrity System, Internal Control System and Leadership Practices: A Review Study - Abd Aziz, Mohamad Azizal; Ab Rahman, Hilmi; Alam, Md Mahmudul; Said, Jamaliah (Elsevier B.V., 2015)
Currently, governance in public administration has become a global issue as a result of the continuous stream of governance failures, fraud, inefficiency, corruption, and poor internal control and financial management.Public sectors worldwide are now under pressure to justify the sources and utilization's of public resources as well as improving the performance in their services delivery.Now it is considered as public rights to monitor the transparency and efficiency of public administration.To ensure good governance, understanding the way to improve accountability in public sector is very essential. Therefore, to enhance the accountability in the public sector, based on the literature review this study discusses on the organizational internal factors that has influences on accountability; integrity system, internal control system and leadership qualities.This study could assist policy makers to establish more accountability among different departments and agencies of government.